Evaluasi Alinemen Horizontal Pada Ruas Jalan Sumedang-Cijelag Km.Bdg 68+650 - Vanka Muhamad Nur Rochman; Ida Farida (Jurnal Konstruksi, 2026)
Road damage caused by landslides on the Sumedang–Cijelag section (Km.BDG 68+650) in March 2022 was rehabilitated by shifting the road alignment. This study aims to evaluate the feasibility and suitability of the horizontal alignment based on the 2021 Bina Marga Road Geometric Design Guidelines. The method used was quantitative with geometric data analysis of the primary collector road (2/2 UD) on flat terrain. The results showed that there were two Spiral-Circle-Spiral type curves with a shift of 0.87 m, each with a circle curve of 43.60 m and 29.99 m and a transition curve of 29 m, all of which met the standards. However, the stopping sight distance (28.42 m) and overtaking sight distance (213.44 m) did not meet the standards (50 m and 270 m, respectively), although the road conditions were still passable with attention to safety signs.